Struktur Dan Konstruksi Bangunan Stasiun KA Kota Lama (Dengan Persandingan Stasiun KA Pasarturi Surabaya) - Sujudwijono, Nurachmad (RUAS, 2013)
Kota Lama Station and Pasar Turi Station built in almost the same period in the early 20th century. The second station was built in the Dutch colonial administration. Both have the same function, namely as a station platform, although it has a different landscape. Wood materials chosen because the wood is readily available resources at the time and is a strong material and commonly used as a building structure. At Pasar Turi Station and the Kota Lama Station using the best wood material, in the form of teak wood with high quality, so that the building can still survive until today. Wood material availability at the time it was still very easy to obtain and are of good quality, in contrast to today, where the wood is a building material that was expensive because its resources are already not as much as before. With the approach of observation and research literature is expected to produce an overview of how the system structure of wood in buildings of Old Town Railway Station can work well and are able to survive until today.Keywords: wood structure, station, wood connection